Immune Profiles Identification by Vaccinomics After MVA Immunization in Randomized Clinical Study - Sanchez, Jorge; Gonçalves, Elena; Llano, Anuska; Gonzáles, Pedro; Fernández-Maldonado, María; Vogt, Annika; Soria, Angele; Perez, Susana; Cedeño, Samandhy; Fernández, Marco Antonio; Nourikyan, Julien; de Bernard, Simon; et al. (Frontiers in Immunology, 2020)
Background Our previous work has demonstrated the benefits of transcutaneous immunization in targeting Langerhans cells and preferentially inducing CD8 T-cell responses. Methods In this randomized phase Ib clinical trial including 20 HIV uninfected volunteers, we compared the safety and immunogenicity of the MVA recombinant vaccine expressing HIV-B antigen (MVA-B) by transcutaneous and intramuscular routes. We hypothesized that the quality of innate and adaptive immunity differs according to the route of immunization and explored the quality of the vector vaccine-induced immune responses. We also investigated the early blood transcriptome and serum cytokine levels to identify innate events correlated with the strength and quality of adaptive immunity. Results We demonstrate that MVA-B vaccine is safe by both routes, but that the quality and intensity of both innate and adaptive immunity differ significantly. Transcutaneous vaccination promoted CD8 responses in the absence of antibodies and slightly affected gene expression, involving mainly genes associated with metabolic pathways. Intramuscular vaccination, on the other hand, drove robust changes in the expression of genes involved in IL-6 and interferon signalling pathways, mainly those associated with humoral responses, and also some levels of CD8 response. Conclusion Thus, vaccine delivery route perturbs early innate responses that shape the quality of adaptive immunity. Clinical Trial Registration http://ClinicalTrials.gov, identifier PER-073-13.